Condiciones de trabajo y satisfacción laboral en la empresa servicios y soluciones inteligentes B & V S.A.C. - Trujillo: 2019 - Benites Vargas, Alan Raúl (2020)
The purpose of this research work is to determine how working conditions influence the job satisfaction of employees of the company Servicios y Soluciones B&V S.A, C, of the city of Trujillo; formulating as a hypothesis that the working conditions positively influence the job satisfaction of the company's employees, it is a descriptive study - cross-sectional, the inductive-deductive and analytical method was applied, to gather the information designed a questionnaire of questions, which is referred to the variables of the problem, said questionnaire was composed of 40 items or questions, which was divided into four dimensions of each variable, being administered to the employees of the company Services and solutions B&V SA, C , from the city of Trujillo; Once the research work was completed, it was concluded that the working conditions of the company Servicios y Soluciones B&V S.A, C have a positive and direct influence on job satisfaction in the same proportionality. As a result, it is necessary to make decisions that improve working conditions, in order to improve job satisfaction, which would have an impact on the work of employees.